Environmental Cost, Perencanaan Pajak, Ukuran Perusahaan, Leverage, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Muhammad Farhan Fadhlurrohman; Eny Kusumawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of environmental costs, tax planning, company size, leverage, and managerial ownership on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Company value is a key indicator in assessing the performance and prospects of a company, so understanding the factors that influence it is important for management, investors, and other stakeholders. The research method used is a quantitative approach with multiple linear regression analysis. The research sample consists of 84 analysis units selected using purposive sampling method based on certain criteria. The results showed that leverage and managerial ownership have a significant effect on firm value, environmental costs, tax planning, and firm size have no effect on firm value. This finding indicates that the lower the leverage level, which means the lower the financial risk, the higher the firm value. The smaller the proportion of managerial ownership, which means reducing agency conflicts between shareholders and management so that the company value is higher. The results of this study are expected to be a reference for companies in managing financial structures and corporate ownership strategies to increase firm value.